The Significance of a Common Idiotype (1F7) on Antibodies against Human Immune Deficiency Virus Type 1 and Hepatitis C Virus - Muller, Sybille; Parsons, Matthew S.; Kohler, Heinz; Grant, Michael (Frontiers in Oncology, 2016)
In this review, we trace the concept and potential functional role of regulatory idiotypes in the immune response to human immunodeficiency virus type 1 (HIV-1), simian immunodeficiency virus, and hepatitis C virus (HCV). A major idiotype involved in these viral infections is recognized and defined by a murine monoclonal antibody (1F7). Antibodies expressing the idiotype defined by 1F7 are dominant in HIV-1 infection and are also found on many broadly neutralizing antibodies against HIV-1. This regulatory idiotypic axis offers opportunities for exploitation in vaccine development for HIV-1, HCV and other chronic viral infections.